Circulating microRNAs in patients with hormone receptor‐positive, metastatic breast cancer treated with dovitinib. Issue 1 (4th October 2017) - Shivapurkar, Narayan; Vietsch, Eveline E.; Carney, Erin; Isaacs, Claudine; Wellstein, Anton
Abstract: Background: Serial analysis of biomarkers in the circulation of patients undergoing treatment ("liquid biopsies") can provide new insights into drug effects. In particular the analysis of cell‐free, circulating nucleic acids such as microRNAs (miRs) can reveal altered expression patterns indicative of mechanism of drug action, cancer growth, and tumor–stroma interactions. Results: Here we analyzed plasma miRs in patients with hormone receptor positive, metastatic breast cancer with prior disease progression during aromatase inhibitor therapy (n = 8) in a phase I/II trial with the multiple tyrosine kinase inhibitor dovitinib (TKI258). Plasma miR levels were measured by quantitative RT‐qPCR before and after treatment with dovitinib. A candidate miR signature of drug response was established from a 379 miR screen for detectable plasma miRs as well as from the published literature. Changes in miR expression patterns and tumor sizes were compared. In this analysis we identified miR‐21‐5p, miR‐100‐5p, miR‐125b‐5p, miR‐126‐3p, miR‐375 and miR‐424‐5p as potential indicators of a response to dovitinib. The altered expression patterns observed for the six circulating miRs separated patients with resistant disease from those with drug responsive disease. There was no relationship between adverse effects of dovitinib treatment and identifiable changes in miR patterns. Conclusion: We conclude that changes in the expression patterns of circulating miRs can be indicators of drug responses that merit prospective studies for validation.